Expression profile of genes as indicators of developmental competence and quality of in vitro fertilization and somatic cell nuclear transfer bovine embryos - Cánepa, María Jesús (2014)
Reproductive biotechnologies such as in vitro fertilization (IVF) and somatic cell nuclear transfer (SCNT) enable improved reproductive efficiency of animals. However, the birth rate of in vitro-derived embryos still lags behind that of their in vivo counterparts. Thus, it is critical to develop an accurate evaluation and prediction system of embryo competence, both for commercial purposes and for scientific research. Previous works have demonstrated that in vitro culture systems induce alterations in the relative abundance (RA) of diverse transcripts and thus compromise embryo quality. The aim of this work was to analyze the RA of a set of genes involved in cellular stress (heat shock protein 70-kDa, HSP70), endoplasmic reticulum (ER) stress (immunoglobulin heavy chain binding protein, Bip; proteasome subunit β5, PSMB5) and apoptosis (BCL-2 associated X protein, Bax; cysteine aspartate protease-3, Caspase-3) in bovine blastocysts produced by IVF or SCNT and compare it with that of their in vivo counterparts. Poly (A) + mRNA was isolated from three pools of 10 blastocysts per treatment and analyzed by real-time RT-PCR. The RA of three of the stress indicators analyzed (Bax, PSMB5 and Bip) was significantly increased in SCNT embryos as compared with that of in vivo-derived blastocysts. No significant differences were found in the RA of HSP70 and Caspase-3 gene transcripts. This study could potentially complement morphological analyses in the development of an effective and accurate technique for the diagnosis of embryo quality, ultimately aiding to improve the efficiency of assisted reproductive techniques (ART).